Possibility of co-protection for populations of steppe and forest plants in alone location: A case study in Republic of Mordovia, Russia - MARIA A. SENCHUGOVA; ANATOLIY A. KHAPUGIN (Biodiversitas Journal of Biological Diversity, 2018)
Senchugova MA, Khapugin AA. 2018. Possibility of co-protection for populations of steppe and forest plants in alone location: a case study in Republic of Mordovia, Russia. Biodiversitas 19: 1387-1395. In conditions of vegetation mosaicity of forest-steppe zone, many threatened plant species from different coenologic groups could growth in spatially close habitats. In this study, we tested whether steppe-related (Iris aphylla) and forest-related (Lilium martagon) plants could inhabit an alone location in conditions of the Republic of Mordovia, Russia. It would allow a probability to establish a Protected Area for preservation of two target plant species. For this purpose, we studied populations of I. aphylla and L. martagon in different locations, including habitats typical and atypical for these species. Using Jacquard similarity index and Tsyganov ecological scales, we compared floristic compositions and environmental variables of all studied locations. As a result, we revealed 25.3%-probability of co-habitation of I. aphylla and L. martagon in conditions of the Republic of Mordovia. Moreover, a proposed habitat was typical for L. martagon. This species has not been found in grassland habitats, while I. aphylla was registered within forest habitats. Obtained results allow to improve the Protected Areas management in the region by organization of a smaller Protected Area by conserving higher number of threatened plant species.